Measuring Health-Related Quality of Life in Vietnamese Patients After Kidney Transplantation - Vu, Le Nguyen; Nghia, Nguyen Quang; Tuan, Tran Minh; Phuong, Tran Ha; Vo, Hoang-Long; Viet, Khai Ninh; Giang, Tran Binh (Frontiers in Surgery, 2021)
Objectives: Considering health-related quality of life (HRQOL) has become an inherent part of patient outcomes in the care and treatment after kidney transplantation (KT). This study aims to measure HRQOL among a representative sample size of patients after KT by using both the Short Form 36 (SF-36) and the Kidney Disease Quality of Life 36 (KDQOL-36). Methods and Results: Data of this cross-sectional design was collected in Organ Transplant Center, Viet Duc University Hospital (Hanoi, Vietnam) from January 2020 to March 2020, and included the patients aged 18 years or over after KT at 6 months, 1 year, and 3 years postoperatively. HRQOL was evaluated through face-to-face interviews by means of SF-36 and KDQOL-36 measurement tools. According to the SF-36, the overall mean score of HRQOL was 69.13 ± 15.55 and two domains were the highest scores of ‘Mental Health’ (81.23 ± 14.28) and ‘General Health’ (80.06 ± 14.81). When measuring with KDQOL-36, the overall mean score was 68.67 ± 13.75 and was the highest in domain ‘Symptoms and Problems of Kidney Disease’ (87.06 ± 16.00). Both two instruments had good reliability for those after KT. The reliability of SF-36 was high with Cronbach’s coefficients α = 0.90. There were positive relationships between the dimentions measured by KDQOL-36 and SF-36 (correlation coefficient: 0.03 to 0.69). Similarly, the domains of the SF-36 also had positive correlations with KDQOL-36’ (correlation coefficient: 0.18 to 0.51). The correlation coefficient between overall HRQOL scores of SF-36 and KDQOL-36 was 0.62, indicating a strong correlation between SF-36 and KDQOL-36. Conclusions: There were slight fluctuations in the HRQOL score in domains in follow-up 3-year stages, suggesting not having clear change. The mean SF-36 score was consistent with the mean KDQOL-36 score. High reliability and strong correlation were found between two instruments of SF-36 and KDQOL-36. The present study provides the reliability and construct validity in the combination of two sets of SF-36 and KDQOL-36 scales for the assessment of HRQOL among post-KT patients, thereby, assisting physicians and health professionals in clinical decision-making, assessment of therapeutic efficacy and understanding of treatment risk.